2014
DOI: 10.1016/j.commatsci.2014.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation of capillary absorption in concrete using a three-dimensional mesoscale approach

Abstract: In many exposure environments, capillary absorption of water controls the rate of deterioration of concrete. This paper presents a three-dimensional numerical investigation of capillary absorption by treating concrete as a heterogeneous composite discretised into a cubic lattice. The lattice elements were considered as conductive "pipes" with transport properties assigned based on the phase they represent. The capillary absorption process was described by a non-linear diffusion equation, with the hydraulic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Published by the Royal Society under the terms of the Creative concrete structures begin to deteriorate when they are in service for several years, owing to factors such as chloride attack, sulfate attack, frost, carbonation, alkali-silica reaction and so on [4][5][6][7][8][9]. During the process of deterioration, water directly participates in much physical deterioration and indirectly takes part in chemical deterioration as a medium of aggressive ions transport [8][9][10][11]. Therefore, the study of water transport in cement-based materials is the basis for their durability research, and it is of great significance to evaluate the properties, predict the service life and improve the design level of durability [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Published by the Royal Society under the terms of the Creative concrete structures begin to deteriorate when they are in service for several years, owing to factors such as chloride attack, sulfate attack, frost, carbonation, alkali-silica reaction and so on [4][5][6][7][8][9]. During the process of deterioration, water directly participates in much physical deterioration and indirectly takes part in chemical deterioration as a medium of aggressive ions transport [8][9][10][11]. Therefore, the study of water transport in cement-based materials is the basis for their durability research, and it is of great significance to evaluate the properties, predict the service life and improve the design level of durability [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…12) seem to be the main explanation for the lower sorptivity of concrete cover observed in the case of SCC formed against PW surfaces compared to PVC surfaces. Indeed capillary pores exist only in the cement matrix [30][31][32]; the presence of locally high volume of coarse aggregate leads to a lower paste content, thus diluting the volume of the porous media through which absorption could occur [7] and delays penetration of water due to the increased tortuosity. …”
Section: Evaluation Of Wall Effectmentioning
confidence: 99%
“…Due to the presence of a formed surface, the change in packing of aggregate at the boundary layer against that surfaces (also known as the wall effect) can affect the in-situ transport properties [7]. Kreijger [8] showed that in the case of conventional vibrated concrete, the material found in the first 5 mm near the formwork is essentially composed of mortar with a water-to-cement ratio (w/c) greater than that found in the bulk concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete is a multi-phase and complex system. Therefore, numerical methods based on multi-species modeling seem very promising for the analysis of concrete [20]. Numerical simulations have been widely used to analyze the influence of aggregates on the transport properties in concrete, including heat transport.…”
Section: Introductionmentioning
confidence: 99%